Islamic Financial Literacy, Inclusion, and MSME Financial Well-Being: The Mediating Role of Islamic Banking Intention - Dhidhin Noer Ady Rahmanto; Agustina Handayani (Universitas Muhammadiyah Sumatera Utara, 2026)
This study examines the effect of Islamic financial literacy and Islamic financial inclusion on the financial well-being of micro, small, and medium enterprises (MSMEs) and analyzes the mediating role of intention to use Islamic banking products. The research was conducted on MSME owners and managers in the trade and industrial sectors in Klaten Regency, Indonesia. Using a quantitative causal-associative design, primary data were collected through offline questionnaires from 100 MSME respondents selected using purposive sampling. The data were analyzed using SPSS 25 and PROCESS Macro Model 4 with bootstrapping. The findings show that Islamic financial literacy has a positive and significant effect on financial well-being and intention to use Islamic banking products. Islamic financial inclusion also has a positive and significant effect on both financial well-being and intention to use Islamic banking products. Intention to use Islamic banking products significantly improves MSME financial well-being. The mediation analysis reveals that intention to use Islamic banking products significantly mediates the relationship between Islamic financial literacy and financial well-being, but does not significantly mediate the relationship between Islamic financial inclusion and financial well-being. These findings indicate that knowledge must be translated into actual intention and usage to improve financial well-being, while access alone is insufficient when product adoption remains limited. The study contributes to Islamic finance literature by integrating financial literacy, financial inclusion, behavioral intention, and financial well-being in a single MSME-based mediation model.